Ileal and cecal microbiota response to Salmonella Typhimurium challenge in conventional and slow-growing broilers - Sheets, Tessa R.; Wickware, Carmen L.; Snyder, Ashlyn M.; Weimer, Shawna L.; Johnson, Timothy A. (Frontiers in Physiology, 2022)
Despite the negative impacts of Salmonella intestinal colonization on human health, Salmonella is a natural colonizer of the gastrointestinal tract and is not overtly pathogenic to the avian host. It is of interest to understand the impacts and colonization rates of Salmonella across selected genetic lines such as slow-growing (SG) and conventional (CONV) broilers. The objective of this study was to characterize the relationship between Salmonella enterica serovar Typhimurium challenge and selected broiler genetic lines on the ileal and cecal microbiome. Male chicks of two broiler breeds (n = 156/breed) were cohoused in an open floor pen until day 7. On day 13, the chicks were then separated into 12 isolators per breed (4 rooms, 6 isolators/room, 11 chicks/isolator). On day 14, chicks in the 12 treatment isolators (6 isolators/breed, 132 total) were challenged with Salmonella Typhimurium (ST) (1x10^8 CFU/ml) via oral gavage while the remaining chicks (n = 132) were given an oral gavage of sterile tryptic soy broth control (C). Ileal and cecal contents were collected on day 7 from 24 chicks of each breed, and on days 13, 17, 21, and 24 from two chicks per isolator. Samples underwent DNA extraction and PCR amplification to obtain 16S rRNA amplicons that were sequenced with Illumina MiSeq. Salmonella Typhimurium colonization in the cecum was not different in the two broiler breeds. The main effect of breed had the greatest impact on the ileum microbiota of broilers 7 days of age where SG broilers had significantly lower diversity and richness compared to CONV broilers (P < 0.05). Salmonella Typhimurium challenge consistently caused a change in beta diversity. Regardless of day or intestinal location, challenged broilers had many amplicon sequence variants (ASVs) with decreased abundance of likely beneficial bacteria such as Mollicutes RF39, Shuttleworthia, Flavonifractor, and Oscillibacter compared to broilers that were unchallenged with Salmonella Typhimurium (P < 0.05). Additionally, there was a difference in the timing of when the microbiota alpha and beta diversity of each breed responded to Salmonella Typhimurium challenge. Thus, both broiler breed and Salmonella Typhimurium can impact the intestinal microbiota.